2013
DOI: 10.1002/jmri.24334
|View full text |Cite
|
Sign up to set email alerts
|

Initial experience of MR/PET in a clinical cancer center

Abstract: Magentic Resonance/positron emission tomography (PET) has been introduced recently for imaging of clinical patients. This hybrid imaging technology combines the inherent strengths of MRI with its high soft-tissue contrast and biological sequences with the inherent strengths of PET, enabling imaging of metabolism with a high sensitivity. In this article, we describe the initial experience of MR/PET in a clinical cancer center along with a review of the literature. For establishing MR/PET in a clinical setting, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 87 publications
(110 reference statements)
0
6
0
Order By: Relevance
“…Moreover, 2 recent studies have shown that PET/MRI alone had a greater impact on clinical management compared to PET/CT alone [ 28 , 29 ]. However we are still awaiting a systematic study PET/MRI in bladder cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, 2 recent studies have shown that PET/MRI alone had a greater impact on clinical management compared to PET/CT alone [ 28 , 29 ]. However we are still awaiting a systematic study PET/MRI in bladder cancer.…”
Section: Discussionmentioning
confidence: 99%
“…It requires radio-labelling of exogenous agents, such as fluoro-deoxyglucose, but can detect signals at much lower concentrations (10 -12 molar) than MRS (mM) and therefore yields complementary information. Recently combined MR-PET systems have become available in which MR and PET data are acquired within the same examination (Partovi et al, 2014, Gaertner et al, 2013). This has required huge technological hurdles to be overcome to avoid serious image degradation in both modalities.…”
Section: Contrast Mechanisms In Mrimentioning
confidence: 99%
“…Moreover, advanced MRI techniques (DWI, DCE and MR spectroscopy) yield functional information that may complement the findings of PET imaging. To date, several PET/MRI studies have shown promising results for clinical oncologic applications [8,9]. The best applications for PET/MRI imaging exist for HNC.…”
Section: Introductionmentioning
confidence: 99%